Heat transfer in crystalline clathrate hydrates at low temperatures: Related Topics - Krivchikov, A.I.; Korolyuk, O.A.; Romantsova, O.O. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2007)
The experimental results on the thermal conductivity к(T) of crystalline Xe, CH4, and THF clathrate hydrates have been analyzed. In a wide region of temperatures above 2 K, к(T) exhibits a behavior typical of disordered solids, which depends weakly on their chemical composition, crystalline structure and microstructure. The results are discussed in the context of phenomenological models of phonon scattering by local modes. It has been found that the Xe clathrate has a feature unusual for glasses, namely, к(T) decreases almost two-fold as the temperature increases from 50–100 K. The behavior of к(T) is presumably determined mainly by the strong phonon scattering on water molecules.